2019
DOI: 10.1001/jamacardio.2019.1510
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 Inhibitor Switching in Response to Routine Notification of CYP2C19 Clopidogrel Metabolizer Status Following Acute Coronary Syndromes

Abstract: IMPORTANCE Physician behavior in response to knowledge of a patient's CYP2C19 clopidogrel metabolizer status is unknown.OBJECTIVE To investigate the association of mandatory reporting of CYP2C19 pharmacogenomic testing, provided to investigators with no direct recommendations on how to use these results, with changes in P2Y12 inhibitor use, particularly clopidogrel, in the Randomized Trial to Compare the Safety of Rivaroxaban vs Aspirin in Addition to Either Clopidogrel or Ticagrelor in Acute Coronary Syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…This regulation is based on the recognition that PGx-guided clopidogrel therapy requires more than just a pharmacogenetic test. Indeed, a subanalysis of the GEMINI-ACS-1 multicenter trial reported that mere routine notification of CYP2C19 metabolizer status resulted in switching to another antiplatelet therapy in only 5.9% of patients with current clopidogrel therapy and intermediate or reduced metabolizer genotype [ 18 ]. In contrast, in a specialized pharmacogenetic program with integrated clinical decision support at the University of Florida, preemptive testing led to implementation of therapy changes in 70.0% of individuals with actionable genotypes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This regulation is based on the recognition that PGx-guided clopidogrel therapy requires more than just a pharmacogenetic test. Indeed, a subanalysis of the GEMINI-ACS-1 multicenter trial reported that mere routine notification of CYP2C19 metabolizer status resulted in switching to another antiplatelet therapy in only 5.9% of patients with current clopidogrel therapy and intermediate or reduced metabolizer genotype [ 18 ]. In contrast, in a specialized pharmacogenetic program with integrated clinical decision support at the University of Florida, preemptive testing led to implementation of therapy changes in 70.0% of individuals with actionable genotypes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of PGx-guided clopidogrel therapy in clinical practice remains a complex challenge [ 18 ]. Our specialized clinical pharmacology services therefore established a comprehensive PGx-guided pharmacotherapy program at two Swiss hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that providers knowledge of patients' CYP2C19 status did not have a significant influence on P2Y12 inhibitor prescription patterns 28,29 . In addition, in the recently published single center ADAPT‐PCI trial, almost half (47%) of patients continued to receive clopidogrel in the genotype group despite loss of function allele in CYP2C19 18 .…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor We read with interest the article by Povsic et al showing the reluctance of physicians to use CYP2C19 genotyping results to guide antiplatelet therapy within the Randomized Trial to Compare the Safety of Rivaroxaban vs Aspirin in Addition to Either Clopidogrel or Ticagrelor in Acute Coronary Syndrome (GEMINI-ACS-1) study. Their data point out a large knowledge gap in that approximately 50% of investigators did not have a plan to alter therapy in genotype-determined nonresponders despite the study being conducted more than 5 years after the US Food and Drug Administration issued a boxed warning about using clopidogrel in poor metabolizers (PMs) homozygous for CYP2C19 nonfunctional alleles.…”
mentioning
confidence: 99%